Visuo-spatial orienting during active exploratory behavior: Processing of task-related and stimulus-related signals. (May 2018) - Macaluso, Emiliano; Ogawa, Akitoshi
Abstract: Functional imaging studies have associated dorsal and ventral fronto-parietal regions with the control of visuo-spatial attention. Previous studies demonstrated that the activity of both the dorsal and the ventral attention systems can be modulated by many different factors, related both to the stimuli and the task. However, the vast majority of this work utilized stereotyped paradigms with simple and repeated stimuli. This is at odd with any real life situation that instead involve complex combinations of different types of co-occurring signals, thus raising the question of the ecological significance of the previous findings. Here we investigated how the brain responds to task-related and stimulus-related signals using an innovative approach that involved active exploration of a virtual environment. This enabled us to study visuo-spatial orienting in conditions entailing a dynamic and coherent flow of visual signals, to some extent analogous to real life situations. The environment comprised colored/textured spheres and cubes, which allowed us to implement a standard feature-conjunction search task (task-related signals), and included one physically salient object that served to track the processing of stimulus-related signals. The imaging analyses showed that the posterior parietal cortex (PPC) activated when the participants' gaze was directed towards the salient-objects. By contrast, the right inferior partial cortex was associated with the processing of the target-objects and of distractors that shared the target-color and shape, consistent with goal-directed template-matching operations. The study highlights the possibility of combining measures of gaze orienting and functional imaging to investigate the processing of different types of signals during active behavior in complex environments.